2020
DOI: 10.1002/cssc.202000268
|View full text |Cite
|
Sign up to set email alerts
|

Response of Pseudomonas putida to Complex, Aromatic‐Rich Fractions from Biomass

Abstract: There is strong interest in the valorization of lignin to produce valuable products; however, its structural complexity has been a conversion bottleneck. Chemical pretreatment liberates lignin‐derived soluble fractions that may be upgraded by bioconversion. Cholinium ionic liquid pretreatment of sorghum produced soluble, aromatic‐rich fractions that were converted by Pseudomonas putida (P. putida), a promising host for aromatic bioconversion. Growth studies and mutational analysis demonstrated that P. putida g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 79 publications
(169 reference statements)
0
17
0
Order By: Relevance
“…Pseudomonas putida KT2440 is an important metabolic engineering chassis, which can readily metabolize compounds derived from lignocellulosic and plastic derived feedstocks (1)(2)(3), and has an ever-growing repertoire of advanced tools for genome modification (4)(5)(6)(7). Its upper glycolytic pathway architecture enables P. putida to natively generate large amounts of reducing equivalent (8), and it more robustly withstands metabolic burdens than many other frequently used host organisms (9).…”
Section: Importance Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas putida KT2440 is an important metabolic engineering chassis, which can readily metabolize compounds derived from lignocellulosic and plastic derived feedstocks (1)(2)(3), and has an ever-growing repertoire of advanced tools for genome modification (4)(5)(6)(7). Its upper glycolytic pathway architecture enables P. putida to natively generate large amounts of reducing equivalent (8), and it more robustly withstands metabolic burdens than many other frequently used host organisms (9).…”
Section: Importance Introductionmentioning
confidence: 99%
“…Amongst the most important metabolisms not yet rigorously interrogated via omics-level analyses are fatty acid and alcohol degradation. Recently, fatty acids have been shown to be a non-trivial component of some feedstock streams (1) and, depending on their chain length, serve as high-value target molecules (21). Furthermore, intermediates in beta-oxidation can be channeled towards mega-synthases to produce more complex molecules (22), or used in reverse beta-oxidation to produce compounds such as medium chain n-alcohols (23).…”
Section: Importance Introductionmentioning
confidence: 99%
“…These microbial consortia were cultivated on untreated and heat-treated wheat straw [22], where lignin proportion is higher, but probably with lower recalcitrance compared to substrates used on the selection of WS1-M, SG-M and CS-M. In a recent proteomic-based study, Park et al [47] demonstrated that P. putida KT2440 significant induces the production of pca-derived proteins after growth on plant-derived lignolysate.…”
Section: Abundance Of Lignin-transforming Enzyme-encoding Genesmentioning
confidence: 99%
“…1 In this regard, during recent decades, microbial conversion of the lignocellulosic-sugars has been studied extensively using various types of microbial hosts for its efficient utilization. Pseudomonas putida KT2440 (KT2440) has garnered attention due to its high inherent tolerance and capability to utilize the aromatic compounds [2][3][4][5][6] which constitute 5-30% of total carbon in lignocellulosic biomass. 7 One of the major difficulties in the bioprocessing of lignocellulosic biomass is due to its recalcitrance and irregular bond structure which limits the overall activity of depolymerizing enzymes.…”
Section: Introductionmentioning
confidence: 99%